2014
DOI: 10.1111/oik.01753
|View full text |Cite
|
Sign up to set email alerts
|

Sexual size dimorphism in island plants: the niche variation hypothesis and insular size changes

Abstract: The niche variation hypothesis predicts insular populations exhibit increased sexual size dimorphism (SSD), to minimize intraspecific competition. Although many animal taxa conform to this prediction, insular patterns of SSD have yet to be investigated in plants. Here, we tested for differences in SSD of dioecious plants that colonised four island groups (Kermadec, Three Kings, Chatham and Auckland Islands) from New Zealand. Using herbarium collections, we quantified leaf and stem sizes of 263 individuals from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…A phenomenon whereby insular populations expand their niches through expansion of intra‐population variation, usually thought to derive through release from interspecific competition, is often termed the “niche variation hypothesis” (Bolnick, Svanbäck, Araújo, & Persson, ; Soule & Stewart, ; Van Valen, ; although the term also have other, related meanings, see, e.g. Costa, Mesquita, Colli, & Vitt, ; Kavanagh & Burns, ). Insular species are hypothesized to have wider niches than mainland ones because they are, presumably, free to exploit resources that on the mainland would be used by their competitors (Dunham, Tinkle, & Gibbons, ; Soule & Stewart, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A phenomenon whereby insular populations expand their niches through expansion of intra‐population variation, usually thought to derive through release from interspecific competition, is often termed the “niche variation hypothesis” (Bolnick, Svanbäck, Araújo, & Persson, ; Soule & Stewart, ; Van Valen, ; although the term also have other, related meanings, see, e.g. Costa, Mesquita, Colli, & Vitt, ; Kavanagh & Burns, ). Insular species are hypothesized to have wider niches than mainland ones because they are, presumably, free to exploit resources that on the mainland would be used by their competitors (Dunham, Tinkle, & Gibbons, ; Soule & Stewart, ).…”
Section: Introductionmentioning
confidence: 99%
“…(), however, found similar or even higher morphological variability in mainland settings, which they ascribed to the influence of gene flow. Kavanagh and Burns () found no evidence for increased sexual size dimorphism (SSD) in island plants compared to mainland ones.…”
Section: Introductionmentioning
confidence: 99%
“…Research from Cox & Burns (2017) has shown that leaves on Chatham Island species showed stronger evidence for island gigantism than plant stature, which was also greater for the island species compared to their closest mainland relative. Kavanagh & Burns (2015) also found that leaves are significantly larger on islands. Other traits, such as seed size has also been demonstrated to increase on islands through inter-specific comparison (Kavanagh & Burns, 2014).…”
Section: Evidence Of Insular Gigantism -Why Might Species Get Bigger?mentioning
confidence: 85%
“…Corner (1949) demonstrated previously that seed size is correlated with traits such as stem size and plant height. Kavanagh & Burns (2015) and Cox & Burns (2017) also found evidence that insular seed size tended to display gigantism, and correlate with plant stature. However, the same studies found that not all traits correlate, and that some, such as leaf size, display size independently of other traits.…”
Section: Possible Confounding Effects Of Trait Allometrymentioning
confidence: 87%
See 1 more Smart Citation